Prevalence, Risk Behaviours, and HIV Knowledge in an Indigenous Community in Colombia (2015)
ABSTRACT: There are 87 Indigenous ethnic groups in Colombia, representing 3.4% of the country’s population. Poverty, forced displacement, and social and health inequities place Indigenous communities at increased risk of HIV/AIDS. However, little is known about the prevalence of HIV in this population. The objectives of this study were to estimate the prevalence of HIV and other sexually transmitted infections in an Indigenous community in Colombia, and to assess community members’ knowledge about the disease and its risk factors. The study, conducted in 2010, was initiated at the request of the leadership of the community of Cristianía and involved community members in all stages of the project. HIV prevalence data were gathered through rapid testing of a random sample of 295 community members between the ages of 15 and 49 years. As well, researchers administered a survey related to sexual behaviours and knowledge about HIV. Findings revealed 3 cases of HIV, a prevalence of 1.02%, 95% CI [0.21, 2.94]. The 3 cases were women. The majority of individuals sampled had heard of HIV or AIDS, but their level of knowledge about the mechanisms of virus transmission varied substantially. The results of this study, the first to explore the prevalence of HIV among Indigenous people within a community in Colombia, suggest a need to investigate HIV prevalence within other Indigenous communities in Colombia.